2017
DOI: 10.1016/j.neurobiolaging.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microbleeds and risk of incident dementia: the Framingham Heart Study

Abstract: Cerebral microbleeds (CMB) are MRI markers attributed to the most common cerebral angiopathies in the elderly and in patients with dementia: hypertensive and cerebral amyloid angiopathy (CAA). CMB detection in asymptomatic persons may help identify those at risk for dementia, and may influence preventive strategies and design of clinical trials testing treatments for dementia. We studied the association of CMB with risk of incident dementia in community dwelling individuals. 1296 dementia-free Framingham Heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 35 publications
0
36
0
3
Order By: Relevance
“…The literature suggests that the presence of four or more microbleeds may increase the risk of cognitive decline and dementia [12,13]. Most patients in this study did not have a worsening of their cognitive function or signs of neurologic impairment at their follow-up visit in the clinic, suggesting that the increase in CMB count in this patient population with pre-existing microbleeds was essentially subclinical.…”
Section: Discussionmentioning
confidence: 57%
“…The literature suggests that the presence of four or more microbleeds may increase the risk of cognitive decline and dementia [12,13]. Most patients in this study did not have a worsening of their cognitive function or signs of neurologic impairment at their follow-up visit in the clinic, suggesting that the increase in CMB count in this patient population with pre-existing microbleeds was essentially subclinical.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, the presence of lobar microbleeds may suggest cerebral amyloid angiopathy [14]. These small vessel markers are predictive of future dementia risk (as well as stroke and mortality risks) [15][16][17] and represent potentially treatable or preventable targets that could reduce dementia expression. Although there are currently few studies comparing the accu-racy of CT and MRI to detect a vascular component to dementia [18], Beynon et al [19] found greater accuracy of MRI compared to CT for lacunar infarcts, non-lacunar infarcts, white matter hyperintensities, periventricular hyperintensities, basal ganglia hyperintensities, and global assessment (presence of two or more findings).…”
Section: Introductionmentioning
confidence: 99%
“…Фибрилляция предсердий (ФП) представляет собой наиболее часто встречающееся в мировых масштабах нарушение ритма сердца, в группе повышенного риска развития данной аритмии находится в среднем один из четырех человек в возрасте старше 40 лет [1]. Другой важной проблемой современного здравоохранения являются когнитивные нарушения (КН) и деменция, которые обнаруживаются у огромного числа людей во всем мире -по состоянию на 2010 г. количество пациентов с деменцией составляло более 35 млн, и, по прогнозам, в ближайшие десятилетия этот показатель будет стремительно увеличиваться [2][3][4]. ФП и КН взаимосвязаны между собой посредством повышенного риска инсульта при данной аритмии, а также в силу общих факторов риска, таких как артериальная гипертензия (АГ), сахарный диабет, сердечная недостаточность, заболевания сосудов и возраст [5,6].…”
unclassified
“…В Роттердамском исследовании (3257 участников, средний возраст 59,6±7,8 года), после поправки на пол, возраст и уровень образования, наличие ЦМК увеличивало риск развития всех типов деменции (ОР 2,02; 95% ДИ 1,25-3,24) и деменции при болезни Альцгеймера (ОР 2,10; 95% ДИ 1,21-3,64) [7]. Аналогичные результаты были получены в субанализе Фрамингемского исследования (1296 участников, средний возраст 72±8 лет): у лиц с ЦМК отмечалось увеличение риска деменции практически в 2 раза (ОР 1,74; 95% ДИ 1,00-3,01) [4]. В работе Y. Yakushiji и соавт.…”
unclassified
See 1 more Smart Citation